Design Of Safety Signs Using Ergonomic Function Deployment Method At PT.XYZ - Dita Kusuma Ningsih; Heriyono Lalu; Sheila Amalia Salma (International Journal of Innovation in Enterprise System, 2022)
PT. XYZ is a company engaged in manufacturing by processing raw materials into semi-finished goods or finished goods. Because the company routinely produces these products and involves machinery, it will allow small to serious work accidents to occur. Based on the hazard event data owned by the company, there are 5 very diverse events that will be analyzed in the risk control hierarchy to minimize hazard events. The results of the risk control hierarchy analysis have two hazard events that have safety sign design criteria. Therefore, research was conducted to design safety signs in the area of explosive materials and loading progress in minimizing hazard events using safety signs assessment and Ergonomic Function Deployment approaches. The data needed in the design are anthropometric data, layout data, customer statements and level questionnaires interest and satisfaction. From the results of the safe sign assessment, the signal word is obtained, determining the location, height, model, and material of the safety signs. The results of the safety signs assessment will be used for the Ergonomic Function Deployment approach. From the results of the Ergonomic Function Deployment, the results obtained are the size of safety signs, safe reading distance, type of layout, use of language and font size on safety signs. There are two types of designs, namely explosive material and loading progress safety signs. The design of safety signs refers to the ANSI Z535 standard so that the design of safety signs has detailed signal words, symbols, signs, and word messages.